Faktor Pendorong Komitmen Nasabah dalam Pengembalian Dana Pembiayaan di BMT UGT Sidogiri - Rozi, A. Fahrur; Amalia, Fika; Muhammad, Helmi (Universitas Islam Raden Rahmat, 2022)
This research is motivated by the instability of customer commitment in returning financing funds at BMT UGT Sidogiri Pagak Sub-Branch, Malang Regency. The context of the research in this study is